ANALISIS PERBANDINGAN RENCANA ANGGARAN BIAYA STRUKTUR PELAT LANTAI KONVENSIONAL DENGAN SISTEM FLOOR DECK - Sahid, Muh Nur; Priyanto, Budi; Winardi, Winardi (Eco Rekayasa: Jurnal Teknik Sipil, 2015)
This study is intended for comparison of the structure of a conventional floor slab and floor deck system. The aim of research looking for an easy job execution, performance and productivity of labor and equip-ment are high, the effectiveness of a faster time and low cost of the two methods. Object of research on Building Project National Craft Council and Scout (DESPRA) Central Java, Semarang. This comparative study covers the analysis of the implementation of the work, the analysis of the performance and produc-tivity of labor and equipment, timing analysis, the cost of implementation with field observation method. Implementation of research results slab floor deck system more effective and efficient both from the level of difficulty and time required compared to conventional floor plate. Labor productivity and higher tool structure floor deck slab system compared to conventional floor plate structure. While the performance of slab floor deck system is better than the conventional floor plate. The timing of the slab floor deck system faster than conventional floor plate difference of 6.92 days. Costs on the work floor deck slab system less than a conventional floor plates by a margin of 8.105%